Analysing markets within the latent class approach: an application to the pharma sector. (2nd March 2012) - Bassi, Francesca
<x xml:space="preserve">Abstract</x> In this paper, the latent class approach is applied to an analysis of the Italian pharmaceutical market. The application serves as an example of how fruitfully latent class methodology can be implemented in marketing research. The sector in question shows a high level of competitiveness, more limited economic budgets than years ago and, at the same time, expensive sales and promotion activities; in this context, it is very important to know the reference market to design appropriate marketing strategies. Taking into account the hierarchical structure of the data, this paper: (i) identifies groups of doctors with similar attitudes toward pharmaceutical representatives' work and (ii) verifies which aspects of promotional activity are significant to influence prescription quantities. Copyright © 2012 John Wiley & Sons, Ltd.